Notes on the impact factor of journal, citation index and quality of a published scientific paper - Long, Khuat Dang (Academia Journal of Biology, 2012)
This paper presented an overview of the journal impact factors, citation index and discussed about the limitations of using the journal impact factor for the evaluation of the quality of papers and the researchers who wrote those papers without considering the real contribution of co-authors in multi-author research papers published in a journal. The paper also showed an analysis of viewpoints of different authors about the use and abuse of impact factors based on data of the ISI® Journal Citation Reports (JCR®) in recent years.